Penerapan alat pengering hybrid dalam meningkatkan produktivitas dan higienitas ikan sepat kering - Dessy Maulidya Maharani; Agung Nugroho; Agung Cahyo Legowo (DEDIKASI, 2019)
The increasing price of Sepat salty fish during rain season is one problem of food producers in Martapura city. Higher price mostly caused of decreasing ability to dry out the fish. In addition, The product of salty fish is not hygienic because of unprotected process from dust and insect. The solving of this problem is modification of dried fish process using Hybrid drying machine (solar-stove combination). The aim of this programme are improving community knowledge about the fish nutrition value, educating community on hygienic drying methods, increasing of dry fish productivity and improving community knowledge on diversification product of salt fish. The target community for this programme is in the Tambak Baru ulu village of Martapura district of Banjar regency. The Methods of this programme are courses, discussions and training. The results of this community services activities showed that the community get knowledge about the nutritional value of Sepat Fish, skills to dry fish using a Hybrid dryer, increases dry fish productivity during rain season and ability to diversify of dry fish products.